Inflammatory Disequilibrium in Stroke. Issue 1 (24th June 2016) - Petrovic-Djergovic, Danica; Goonewardena, Sascha N.; Pinsky, David J.
Abstract : Over the past several decades, there have been substantial advances in our knowledge of the pathophysiology of stroke. Understanding the benefits of timely reperfusion has led to the development of thrombolytic therapy as the cornerstone of current management of ischemic stroke, but there remains much to be learned about mechanisms of neuronal ischemic and reperfusion injury and associated inflammation. For ischemic stroke, novel therapeutic targets have continued to remain elusive. When considering modern molecular biological techniques, advanced translational stroke models, and clinical studies, a consistent pattern emerges, implicating perturbation of the immune equilibrium by stroke in both central nervous system injury and repair responses. Stroke triggers activation of the neuroimmune axis, comprised of multiple cellular constituents of the immune system resident within the parenchyma of the brain, leptomeninges, and vascular beds, as well as through secretion of biological response modifiers and recruitment of immune effector cells. This neuroimmune activation can directly impact the initiation, propagation, and resolution phases of ischemic brain injury. To leverage a potential opportunity to modulate local and systemic immune responses to favorably affect the stroke disease curve, it is necessary to expand our mechanistic understanding of the neuroimmune axis in ischemic stroke. This review explores the frontiers of current knowledge of innate and adaptive immune responses in the brain and how these responses together shape the course of ischemic stroke.